Doctor strange by mark waid, volume 4 ebook - Howard, Tini (Doctor Strange (2018), 2020)
Collects Doctor Strange (2018) #18-20, Doctor Strange Annual (2019) #1. A major turning point for Doctor Strange! Stephen Strange is back on Earth, safe and sound after his otherworldly odyssey with Galactus and Clea — but is the Multiverse done with Stephen Strange? A truly terrifying villain is working their way into the Marvel Universe via a small house in Kansas, and their arrival will have people talking for years! Stephen Strange's life was changed decades ago by a car crash in upstate New York — but now, his life is about to change in an even bigger way. Plus: The Sanctum Sanctorum holds all of the bizarre and dark relics that Doctor Strange has accumulated on his journey as the Sorcerer Supreme. But when one of those relics awakens, will the Sanctum be transformed into Strange's own personal hell?